DINAMIKA KONSEP “UMMATAN WASATHAN”: PENDEKATAN HERMEUNETIKA MA’NA CUM MAGHZA TERHADAP QS. AL-BAQARAH [2]:143 - Aini Mutmainnah (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
The concept of religious moderation is a trendy issue that is hotly debated, the idea of religious moderation is taken from the Lafadz "Ummatan Wasathan" in QS. Al-Baqarah [2]:143. This paper aims to explore the purpose and meaning of religious moderation from the word Ummatan Wasathan in QS. Al-Baqarah [2]:143 with research using the Ma'na Cum Maghza hermeunetic approach. This research is a literature study in which the primary source is in the form of Al-Quran verses surat Al-Baqarah [2]:143 secondary data sourced from several books of interpretation. The result of this research is that QS Al Baqarah [2]:143 is a response to the Companions' concerns about Allah's decree to move the position of the Qibla from Baitul Maqdis to Masjidil Haram. The phrase "Washatiyah" in "Ummatan Wasthan" is interpreted as the middle and righteous people or ta'adul. In contemporary interpretations, wasath is interpreted as moderate, where Islam is in a position of tawazun, i'tidal and 'is (balance and justice).